Pre and post-settlement support systems and the failure of some land reform projects in South Africa : implications for planning of land reform in the future - Phasha, D.; Moyo, T. (International Conference on Public Administration and Development Alternatives (IPADA), 2020)
The purpose of land reform in South Africa was to correct the injustices of the apartheid era where millions of blacks were dispossessed of their land. A major challenge has been the failure of many projects on land reform projects. Some scholars attribute the failure largely to the provision of inadequate pre and postsettlement support. The paper therefore aims to analyse that support and its contribution to failure of some land reform projects. The objectives are to examine the machineries for the delivery of settlement support, the nature of support and also to analyse its performance. The methodology was a qualitative desk study. Findings pointed to weak institutional capacities in planning and implementation and poor inter-governmental collaboration as key factors for failure. The paper recommends that as the country considers how it will implement the 'Land. Expropriation Without Compensation' policy, the government should significantly invest in an effective, comprehensive and integrated support system of support to beneficiaries to guarantee the success of land reform.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Land reform; Land Expropriation; Pre and post settlement support; Sustainable development; Land reform; Economic development; Apartheid